Assessment of glycemic control and correlation of HbA1c level with lipid profile and duration of diabetes in type 2 diabetes mellitus patients (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: The prevalence of Type 2 diabetes mellitus, or Type 2 DM, is rising globally. A periodic estimation of HbA1c has been recommended to track the state of glycemic control of Type 2 DM patients, in order to control the diabetes associated disorders. The main consequence and cause of death in Type 2 diabetes has been identified as cardiovascular disease (CVD).Optimization of glycemic status along with decreasing CVD risk factors are critical to preventing morbidity and mortality in patients with Type 2 DM. Since there is a lack of data on these CVD risk factors, in Madhesh Province, Nepal, we aimed to evaluate the glycemic status, estimate the lipid profile, and ascertain their correlation, including duration of Type 2 DM among patients in tertiary care hospitals in Madhesh Province, Nepal.Materials and Methods: The tertiary care hospital based cross-sectional study was conducted on 139 Type 2 DM patients, in Madhesh Province, Nepal. In order to gather information of the participants, a systematic questionnaire was introduced. A physical and clinical examination was performed, and an appropriate volume of blood was drawn with prior written consent. The lipid profile parameters, HbA1C, Fasting and post prandial serum glucose were estimated.Results: In 84 (60.3%) and 106 (76.3%) cases, there was an increased fasting and postprandial blood sugar. The mean±SD HbA1c level was 8.40±0.8%. More than half (52.5%) of the patients had poor glycemic control, while 22.3% had inadequate glycemic control, in reference to HbA1c >8% and 7 to 8%, respectively. A substantial increased level of LDL-C, triglycerides and total cholesterol was observed in 122 patients and 85.6% had reduced HDL-C. A significant strong positive association was found between HbA1c level and total cholesterol and triglycerides, in contrast, no discernible association with duration of disease observed.Conclusion: Glycemic control was inadequate. Triglycerides and total cholesterol were significantly positively correlated with HbA1c, but not with HDL-C, LDL-C, or the course of diabetes.